Preparation of a new adsorbent from activated carbon and carbon nanofiber (AC/CNF) for manufacturing organic-vacbpour respirator cartridge - Jahangiri, Mehdi (BioMed Central, 2013)
In this study a composite of activated carbon and carbon nanofiber (AC/CNF) was prepared to improve the performance of activated carbon (AC) for adsorption of volatile organic compounds (VOCs) and its utilization for respirator cartridges. Activated carbon was impregnated with a nickel nitrate catalyst precursor and carbon nanofibers (CNF) were deposited directly on the AC surface using catalytic chemical vapor deposition. Deposited CNFs on catalyst particles in AC micropores, were activated by CO(2) to recover the surface area and micropores. Surface and textural characterizations of the prepared composites were investigated using Brunauer, Emmett and Teller’s (BET) technique and electron microscopy respectively. Prepared composite adsorbent was tested for benzene, toluene and xylene (BTX) adsorption and then employed in an organic respirator cartridge in granular form. Adsorption studies were conducted by passing air samples through the adsorbents in a glass column at an adjustable flow rate. Finally, any adsorbed species not retained by the adsorbents in the column were trapped in a charcoal sorbent tube and analyzed by gas chromatography. CNFs with a very thin diameter of about 10-20 nm were formed uniformly on the AC/CNF. The breakthrough time for cartridges prepared with CO(2) activated AC/CNF was 117 minutes which are significantly longer than for those cartridges prepared with walnut shell- based activated carbon with the same weight of adsorbents. This study showed that a granular form CO(2) activated AC/CNF composite could be a very effective alternate adsorbent for respirator cartridges due to its larger adsorption capacities and lower weight.